LAYANAN BIMBINGAN KONSELING DAN TEORI HOLLAND DALAM PEMILIHAN KARIR DI SEKOLAH - Nurul Aprilia Fitra; Daharnis Daharnis; Nurfarhanah Nurfarhanah (Universitas Negeri Padang, 2023)
Using Holland's theory, or Personality Type Theory, this research examines how counseling services play an important role in helping students overcome problems and make career decisions. This research uses literature research methods and collects information from various sources, such as academic journals, books, and document. Guidance counseling practitioners must understand Holland's theory and apply it in everyday life. This research can also serve as a basis for creating better guidance and counseling programs that help students choose careers.